Key tumor suppressor genes inactivated by "greater promoter" methylation and somatic mutations in head and neck cancer - Guerrero-Preston, Rafael; Michailidi, Christina; Marchionni, Luigi; Pickering, Curtis R; Frederick, Mitchell J; Myers, Jeffrey N; Yegnasubramanian, Srinivasan; Hadar, Tal; Noordhuis, Maartje G; Zizkova, Veronika; Fertig, Elana; Agrawal, Nishant; et al. (Epigenetics, 2014)
Tumor suppressor genes (TSGs) are commonly inactivated by somatic mutation and/or promoter methylation; yet, recent high-throughput genomic studies have not identified key TSGs inactivated by both mechanisms. We pursued an integrated molecular analysis based on methylation binding domain sequencing (MBD-seq), 450K Methylation arrays, whole exome sequencing, and whole genome gene expression arrays in primary head and neck squamous cell carcinoma (HNSCC) tumors and matched uvulopalatopharyngoplasty tissue samples (UPPPs). We uncovered 186 downregulated genes harboring cancer specific promoter methylation including PAX1 and PAX5 and we identified 10 key tumor suppressor genes (GABRB3, HOXC12, PARP15, SLCO4C1, CDKN2A, PAX1, PIK3AP1, HOXC6, PLCB1, and ZIC4) inactivated by both promoter methylation and/or somatic mutation. Among the novel tumor suppressor genes discovered with dual mechanisms of inactivation, we found a high frequency of genomic and epigenomic alterations in the PAX gene family of transcription factors, which selectively impact canonical NOTCH and TP53 pathways to determine cell fate, cell survival, and genome maintenance. Our results highlight the importance of assessing TSGs at the genomic and epigenomic level to identify key pathways in HNSCC, deregulated by simultaneous promoter methylation and somatic mutations.
Keywords: Promoter Regions, Genetic; PAX5 Transcription Factor; Humans; CpG Islands; Mutation; Gene Silencing; Head and Neck Squamous Cell Carcinoma; DNA methylation; nádory hlavy a krku; nádorové buněčné linie; Cohort Studies; DNA Methylation; integration analysis; Carcinoma, Squamous Cell; metylace DNA; Tumor Suppressor Genes; umlčování genů; mužské pohlaví; CpG ostrůvky; spinocelulární karcinom; Tumor Suppressor Protein p53; aktivátorový protein specifický pro B-buňky; receptor Notch1; somatic mutations; promotorové oblasti (genetika); nádorový supresorový protein p53; Receptor, Notch1; ženské pohlaví; transkripční faktory paired box; lidé; Head and Neck Neoplasms; kohortové studie; tumor supresorové geny; mutace; Paired Box Transcription Factors; Male; Cell Line, Tumor; Genes, Tumor Suppressor; Female